2014
DOI: 10.3233/jpd-140410
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral Administration of the Selective Inhibitor of Soluble Tumor Necrosis Factor (TNF) XPro®1595 Attenuates Nigral Cell Loss and Glial Activation in 6-OHDA Hemiparkinsonian Rats

Abstract: Background: Parkinson's disease (PD) is a complex multi-system age-related neurodegenerative disorder. Targeting the ongoing neuroinflammation in PD patients is one strategy postulated to slow down or halt disease progression. Proof-of-concept studies from our group demonstrated that selective inhibition of soluble Tumor Necrosis Factor (solTNF) by intranigral delivery of dominant negative TNF (DN-TNF) inhibitors reduced neuroinflammation and nigral dopamine (DA) neuron loss in endotoxin and neurotoxin rat mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
74
1
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 86 publications
(83 citation statements)
references
References 53 publications
7
74
1
1
Order By: Relevance
“…In previous studies, the concentration of XPro1595 in CSF and plasma were found to be 1–6 ng/ml and 1–8 µg/ml, respectively, after subcutaneous treatment of rats with 10 mg/kg XPro1595 (Barnum et al, 2014). A 10-fold higher level of XPro1595, as used here, would be expected to exchange 99% of endogenous sTNFα (Steed et al, 2003).…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…In previous studies, the concentration of XPro1595 in CSF and plasma were found to be 1–6 ng/ml and 1–8 µg/ml, respectively, after subcutaneous treatment of rats with 10 mg/kg XPro1595 (Barnum et al, 2014). A 10-fold higher level of XPro1595, as used here, would be expected to exchange 99% of endogenous sTNFα (Steed et al, 2003).…”
Section: Discussionmentioning
confidence: 93%
“…The concentration of XPro1595 in the CSF (1–6 ng/ml) has been found to be 1000-fold reduced compared with that in the plasma (1–8 µg/ml) from rats after 2–3 d of treatment with XPro1595 (10 mg/kg s.c.; Barnum et al, 2014). Furthermore, as in the model of SCI, in which acute inflammatory response occurs rapidly in the CNS, the protein levels of TNFα and other inflammatory cytokines increase rapidly in the hippocampus after TMEV infection.…”
Section: Resultsmentioning
confidence: 99%
“…Further investigation may reveal that modulating these multiple mechanisms of sTNF may be contributing to the overall effects on LTP and immune cell trafficking. Our group has shown that peripherally administered XPro1595 gets across the BBB and is able to sequester the picomolar levels of sTNF within the brain (Barnum et al, 2014); however, a recent clinical study with a non-BBB crossing TNF inhibitor (etanercept), implicates a TNF-dependent peripheral mechanisms in the cognitive decline associated with AD pathogenesis (Butchart et al, 2015). Together, these data suggest that TNF can have both direct effects on synaptic physiology as well as indirect effects on peripheral cytokines and immune cell traffic to the CNS and brain resident immune cells and thus, targeting sTNF centrally and peripherally may afford added advantage to improve functional outcomes in patients with AD.…”
Section: Discussionmentioning
confidence: 99%
“…XPro1595 is a PEG-ylated human TNF variant devoid of TNF receptor-binding activity that forms heterotrimers with native sTNF (but not membrane-bound TNF), thereby sequestering sTNF away from TNF receptors (Steed et al, 2003; Barnum et al, 2014). To assess the role of sTNF in AD-like pathology and immune cell trafficking to the CNS, Tg female mice were divide into two cohorts each with two treatment groups.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation